2020
DOI: 10.1097/md.0000000000020802
|View full text |Cite
|
Sign up to set email alerts
|

Big data-based identification of methylated genes associated with drug resistance and prognosis in ovarian cancer

Abstract: It is imperative to further the understanding of the drug resistance mechanisms of ovarian cancer (OC) and to identify useful biological markers for prognosis prediction. Cormine, cBioportal, and The Cancer Genome Atlas databases were used to search microarray data of gene methylation related to OC, drug resistance in OC, and prognosis, and to analyze methylated genes potentially inducing the drug resistance in OC. Fifty-five DNA-methylated genes significantly associated with drug resistance in OC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…PIK3C2B can control cell invasion partly by regulating the MEK/ERK pathway and partly by activating additional signalling pathways that modulate prostate cancer cell migration 33 . And in a previous study, PIK3C2B had impacts on prognostic OS of ovarian cancer(OC), resulting in a reduction in the median survival time of OC by 7 to 10 months 34 . Then PIK3C2B participates in PI3K-Akt signaling pathway, and PI3K network belongs to the most common events in human cancers 34 , Philip et al reported that inhibition of PI3K/Akt/mTOR signaling increased the sensitivity of endometrial carcinoma cells to some targeted therapies 35 , so blocking PIK3C2B may be an immunotherapeutic pathway for the treatment of endometrial carcinoma.…”
Section: Igsf3 (Immunoglobulin Superfamily Member 3) Is a Protein Cod...mentioning
confidence: 90%
“…PIK3C2B can control cell invasion partly by regulating the MEK/ERK pathway and partly by activating additional signalling pathways that modulate prostate cancer cell migration 33 . And in a previous study, PIK3C2B had impacts on prognostic OS of ovarian cancer(OC), resulting in a reduction in the median survival time of OC by 7 to 10 months 34 . Then PIK3C2B participates in PI3K-Akt signaling pathway, and PI3K network belongs to the most common events in human cancers 34 , Philip et al reported that inhibition of PI3K/Akt/mTOR signaling increased the sensitivity of endometrial carcinoma cells to some targeted therapies 35 , so blocking PIK3C2B may be an immunotherapeutic pathway for the treatment of endometrial carcinoma.…”
Section: Igsf3 (Immunoglobulin Superfamily Member 3) Is a Protein Cod...mentioning
confidence: 90%
“…PIK3C2B is strongly related to tumour stage and vessel invasion, which was closely and positively connected with prognosis in colon cancer 31 .In addition, PIK3C2B can regulate different cell functions, such as cell proliferation, invasion and cancer progression 32 .PIK3C2B can control cell invasion partly by regulating the MEK/ERK pathway and partly by activating additional signalling pathways that modulate prostate cancer cell migration 32 .And in a previous study,PIK3C2B had impacts on prognostic OS of ovarian cancer(OC), resulting in a reduction in the median survival time of OC by 7 to 10 months 33 .Then PIK3C2B participates in PI3K-Akt signaling pathway,and PI3K network belongs to the most common events in human cancers 33 ,Philip et al reported that inhibition of PI3K/Akt/mTOR signaling increased the sensitivity of endometrial carcinoma cells to some targeted therapies 34 ,so blocking PIK3C2B may be an immunotherapeutic pathway for the treatment of endometrial carcinoma.…”
Section: 7 | Genetic Alteration Analysis In Patients With Ecmentioning
confidence: 98%
“…Mirkin et al have shown that cisplatin-resistant ovarian cancer cells express higher amounts of MDK than their drug-sensitive counterpart [19]. Big data-based identification and bioinformatics analysis have found the association of MDK as one of the 55 genes that are involved in the development, progression, and drug resistance of ovarian cancer [60].…”
Section: Ovarian Cancermentioning
confidence: 99%